Asociación entre gastritis folicular y Helicobacter pylori en niños atendidos en un hospital público peruano - Vera, C A (2016)
BACKGROUND: For the last 15 years, infection from Helicobacter pylori (H. pylori) has been recognized in gastritis pathogenesis, and is known to trigger an important inflammatory response in these patients. AIM: To determine the association between follicular gastritis and the infection of H. pylori in children seen at a public hospital in Peru. METHODOLOGY: An analytic, cross-sectional study was conducted on all the children treated at the Hospital Nacional Docente Madre "Niño San Bartolomé" in Lima, Peru, within the time frame of 2011-2012. All the personal data from the patients' medical histories and endoscopic procedures were collected. The crude prevalence ratios (PR) were obtained and adjusted (aPR) with their 95% confidence intervals (95%CI), using generalized linear models with the binomial family and log link function. RESULTS: A total of 123 children met the study criteria. Forty-eight (39%) of the study sample were girls and the mean age of the children was 12 years. H. pylori was present in 44% of the sample and 9% presented with more than 100 bacteria per field (classified as +++). Thirty-five percent of the children had esophagitis due to concomitant reflux. The presence of H. pylori was associated with follicular gastritis (P<.01; PRa: 2.3; 95% CI:1.49-3.49), adjusted by the children's age. CONCLUSIONS: Based on the data analyzed, it was concluded that the children with follicular gastritis had a greater likelihood of having H. pylori than those that did not present with gastritis. These results can be extrapolated to other similar populations and should be evaluated in each setting so that this does not become a public health problem within the next few years.